The Protocol for the Multi-Ethnic, multi-centre raNdomised controlled trial of a low-energy Diet for improving functional status in heart failure with Preserved ejection fraction (AMEND Preserved) - Noelle Robertson; Melanie J Davies; Thomas Yates; Gerry P McCann; Gaurav Singh Gulsin; Emer M Brady; Joanne V Wormleighton; Eylem Levelt; Oliver Rider; Jiliu Pan; Christopher Miller; Iain Squire; et al. (BMJ Open)
Introduction Heart failure with preserved ejection fraction (HFpEF) is characterised by severe exercise intolerance, particularly in those living with obesity. Low-energy meal-replacement plans (MRPs) have shown significant weight loss and potential cardiac remodelling benefits. This pragmatic randomised trial aims to evaluate the efficacy of MRP-directed weight loss on exercise intolerance, symptoms, quality of life and cardiovascular remodelling in a multiethnic cohort with obesity and HFpEF.Methods and analysis Prospective multicentre, open-label, blinded endpoint randomised controlled trial comparing low-energy MRP with guideline-driven care plus health coaching. Participants (n=110, age ≥18 years) with HFpEF and clinical stability for at least 3 months will be randomised to receive either MRP (810 kcal/day) or guideline-driven care for 12 weeks. Randomisation is stratified by sex, ethnicity, and baseline Sodium Glucose Cotransporter-2 inhibitor (SGLT2-i) use, using the electronic database RedCap with allocation concealment. Key exclusion criteria include severe valvular, lung or renal disease, infiltrative cardiomyopathies, symptomatic biliary disease or history of an eating disorder. Participants will undergo glycometabolic profiling, echocardiography, MRI for cardiovascular structure and function, body composition analysis (including visceral and subcutaneous adiposity quantification), Kansas City Cardiomyopathy Questionnaire (KCCQ) and Six-Minute Walk Test (6MWT), at baseline and 12 weeks. An optional 24-week assessment will include non-contrast CMR, 6MWT, KCCQ score. Optional substudies include a qualitative study assessing participants’ experiences and barriers to adopting MRP, and skeletal muscle imaging and cardiac energetics using 31Phosphorus MR spectroscopy.Statistical analysis Complete case analysis will be conducted with adjustment for baseline randomisation factors including sex, ethnicity and baseline SGLT2-i use. The primary outcome is the change in distance walked during the 6MWT. The primary imaging endpoint is the change in left atrial volume indexed to height on cardiac MRI. Key secondary endpoints include symptoms and quality of life measured by the KCCQ score.Ethics and dissemination The Health Research Authority Ethics Committee (REC reference 22/EM/0215) has approved the study. The findings of this study will be published in peer-reviewed journals.Trial registration number NCT05887271.